Trauma of displacement in V.S. Naipaul's selected fictions - Mehni, Masoumeh (2016)
V.S. Naipaul's obsession with displacements has been considered as a melancholic sign of his sense of unbelonging by most of his critics. A permanent exile, a refugee, a homeless citizen of the world, and an extranational writer, are some of the assorted terms used to articulate the dominant perception of him. Some critics embrace him as simultaneously coming from nowhere and everywhere, and other critics consider his prose, or perhaps more precisely, the action of writing them as Naipaul’s home. Naipaul’s obsession by displacement in his works implies that displacement is a traumatic experience for him, an issue which has been ignored by his critics. This research considers displacement in Naipaul’s fictions as a traumatic experience. Taking an interdisciplinary approach to the subject of my thesis, it explores the historical and psychological dimensions of the displacement experience, as well as its literary representations. This study addresses displacement in the fictions from different phases of Naipaul’s writing and focuses on The Mimic Men (1967), In a Free State (1971), and The Enigma of Arrival (1987) through character analysis. In the first step, I depicted displacement as a traumatic experience for the characters by the illness which displacement causes Post Traumatic Stress Disorder. In the second step, I suggested two ways the characters go through to remember their trauma. These ways are two different kinds of memory, namely, “acting out” and “working through”, which are related to repetition. “Acting out” or melancholia is related to repetition compulsion, which is the tendency to repeat something compulsively. There are many different ways a person can “act out” his or her traumatic experiences. Flashbacks, nightmares and compulsive behaviour and words are some common ways of “acting out” trauma by traumatised people. “Working through” or mourning involves repetition with significant difference — “working through” is a controlled, explicit, critically controlled process of repetition. In “working through”, the person tries to gain critical distance on a problem and to distinguish between the past, present and future. Generating countervailing forces to “acting out” and testimony are the ways a traumatised person can “work through” her trauma. I take “acting out” and “working through” as different but not opposite processes. “Acting out” and “working through” may never be totally separated from each other, and the two may always mark or be implicated in each other. Finally, I stated that Naipaul’s trauma of displacement is the symptom of historical displacement of his indentured ancestors. I further argued that Naipaul’s writing is a means of representing the “unclaimed” experiences of his ancestors.